WORKSHOP KOLABORATIF: PENYUSUNAN, VALIDASI DAN UJI COBA BAHAN AJAR TEMATIK BERBASIS ANALISIS KEBUTUHAN SISWA SD - A. Elfikasari; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop project-based thematic teaching materials on the theme of Indonesian Cultural Diversity for fifth-grade elementary school students and assess their feasibility and effectiveness in learning. The development was carried out through the stages of needs analysis, material determination, script preparation, validation, revision, and limited trials. The needs analysis indicated that students require open-ended visual, interactive, and easy-to-understand materials. The resulting product is a mini-module containing cultural diversity material, discussion activities, word search projects, evaluation, and reflection. The results of teacher validation showed that the teaching materials are suitable for use with high scores in the aspects of material suitability, language, and activities, although visualization still needs to be strengthened. The trial showed that students understood the material well, were actively involved in group activities, and showed positive attitudes towards cultural diversity. Teacher and student feedback also confirmed that the open-ended materials are interesting, easy to use, and support the achievement of learning objectives. Overall, the teaching materials proved effective in improving conceptual understanding, learning motivation, and attitudes of respect for diversity.